Hacker News new | past | comments | ask | show | jobs | submit login
Why does a/(b/c) = a(c/b)? (mail-archive.com)
3 points by abhididdigi on Nov 21, 2014 | hide | past | favorite | 1 comment



I often find the following analogy useful to have in mind

  a-(b-c) = a+(-b+c) = a+(c-b)

  a/(b/c) = a*(/b*c) = a*(c/b)

  a*(/b*c) is not legal syntax in most languages, but why not?




Consider applying for YC's Spring batch! Applications are open till Feb 11.

Guidelines | FAQ | Lists | API | Security | Legal | Apply to YC | Contact

Search: